2017
DOI: 10.1016/j.cortex.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of emotional source context during memory retrieval

Abstract: Recapitulation involves the reactivation of cognitive and neural encoding processes at retrieval. In the current study, we investigated the effects of emotional valence on recapitulation processes. Participants encoded neutral words presented on a background face or scene that was negative, positive or neutral. During retrieval, studied and novel neutral words were presented alone (i.e., without the scene or face) and participants were asked to make a remember, know or new judgment. Both the encoding and retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
43
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 65 publications
8
43
1
Order By: Relevance
“…Memories for emotional events—negative events in particular—are often accompanied by a feeling of re-experience [4; 5] potentially driven by greater recapitulation of those encoding processes at the time of retrieval. In our prior work [6] we demonstrated that recollected verbal stimuli previously encoded in a negative pictorial context indeed showed more encoding-to-retrieval overlap compared to stimuli encoded in a positive or neutral context. Further, consistent with related work from our lab [7] using degraded line-drawing images of previously encoded full color images, we demonstrated that the valence of the previous encoded context led to differences in regions of the brain that showed this recapitulation.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Memories for emotional events—negative events in particular—are often accompanied by a feeling of re-experience [4; 5] potentially driven by greater recapitulation of those encoding processes at the time of retrieval. In our prior work [6] we demonstrated that recollected verbal stimuli previously encoded in a negative pictorial context indeed showed more encoding-to-retrieval overlap compared to stimuli encoded in a positive or neutral context. Further, consistent with related work from our lab [7] using degraded line-drawing images of previously encoded full color images, we demonstrated that the valence of the previous encoded context led to differences in regions of the brain that showed this recapitulation.…”
Section: Introductionmentioning
confidence: 82%
“…Second, we were interested in examining functional connectivity at retrieval, again with a particular interest in whether valence patterns would emerge in this connectivity. Although the same alternate hypotheses existed for connectivity—there might be minimal, or no, effects of emotion, or the dominant effect might be related to arousal—based on our findings of greater recapitulation of visual processing regions during retrieval of stimuli previously encoded in a negative context [6; 7] and in line with tenants of our “NEVER” model of emotional memory [15], we predicted that network connectivity correlated with visual processing regions would vary by emotional valence and would be stronger for stimuli encoded in a negative context.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations